Risk and Protective Factors Associated With Health-Related Quality of Life of Parents With Mental Illness - Radicke, Alina; Sell, Marlit; Adema, Bonnie; Daubmann, Anne; Kilian, Reinhold; Busmann, Mareike; Winter, Sibylle M.; Lambert, Martin; Wegscheider, Karl; Wiegand-Grefe, Silke (Frontiers in Psychiatry, 2021)
1) Purpose: Health-related quality of life (HRQoL) can be reduced in parents with mental illness (mental illness) who face the dual demands of disabling symptoms and their impact on family, social, and occupational life. This study aimed at analyzing the influence of various factors on HRQoL in parents with mental illness. (2) Method: Baseline data of the German randomized controlled multicenter project CHIMPS (children of parents with mental illness) was used for analyses. The final sample consisted of n = 208 parents with mental illness and n = 197 children and adolescents aged 8-18 years. HRQoL was assessed with the EQ-5D. (3) Results: Parents with mental illness reported significantly lower global and specific HRQoL than the German reference population. They were least satisfied with aspects that relate to anxiety and depression followed by usual activities, pain and discomfort. Better global HRQoL was primarily associated with self-reported physical and mental health, as well as adaptive coping behavior. Associations with mobility, self-care, usual activity, pain and discomfort, anxiety and depression were analyzed and discussed. (4) Conclusions: HRQoL in parents with mental illness is reduced. Clinical interventions should focus on the alleviation of mental health symptoms and probably somatic symptoms and promote adaptive coping skills.